Efficacy of 1-MCP on controlling ethylene sensitivity and extending vase life of sensitive and less sensitive cut orchid flowers - Almasi, Parviz; Mohamed, Mahmud Tengku Muda; Ahmad, Siti Hajar; Noroozisharaf, Alireza (Fundamental and Applied Agriculture, 2019)
This study was conducted to investigate the effects of 1-MCP on the sen- sitivity to ethylene and postharvest quality of selected cut orchid flowers. Cut orchid flowers are considered as the ethylene sensitive but there are ap- parently variation in sensitivity among species, cultivars and hybrids. Low effective concentration of 1- MCP and its minimum residues have caused that 1-MCP been viewed as an important and safe candidate for replacing STS. Inflorescences of each Dendrobium ‘Darren Glory’ (DDG), D. ‘Sonia Bom’ (DSB), Mokara ‘Calypso Jumbo’ (MCJ) and M. ‘Chiti Gold’ (MCG) hybrids were purchased from a commercial farm. After harvest and transport to the Postharvest Lab they were divided into two groups and placed in two chambers. They exposed to 0 and 300 nL L−1 1-MCP for 4 hours. The cham- bers were opened for 1 hour airing. Then inflorescences of each chamber divided to two subgroups and treated with 0 and 1 μL L−1 ethylene gas, balanced with nitrogen. After 24 hours the chambers were opened and the inflorescences were taken out from them. The inflorescences were kept in the laboratory with normal condition. The most weight loss and longest vaselife was recorded in DDG and MCG with 44% and 14 days respectively. Meanwhile, maximum postharvest quality improvement was obtained by 1-MCP pretreatment in very sensitive cut orchid hybrids.